Oxygen Leukocyte Larceny - Pinto da Costa, Miguel (2016)
The authors present a case of a 60-year-old male patient, previously diagnosed with B-cell chronic lymphocytic leukemia, who was admitted to the Emergency Room with dyspnea. The initial evaluation revealed severe anemia (Hgb = 5.0 g/dL) with hyperleukocytosis (800.000/µL), nearly all of the cells being mature lymphocytes, a normal chest X-ray and a low arterial oxygen saturation (89%; pulse oximetry). After red blood cell transfusion, Hgb values rose (9.0 g/dL) and there was a complete reversion of the dyspnea. Yet, subsequent arterial blood gas analysis, without the administration of supplemental oxygen, systematically revealed very low oxygen saturation values (~ 46%), which was inconsistent with the patient’s clinical state and his pulse oximetry values (~ 87%), and these values were not corrected by the administration of oxygen via non-rebreather mask. The investigation performed allowed to establish the diagnosis of oxygen leukocyte larceny, a phenomenon which conceals the true oxygen saturation due to peripheral consumption by leukocytes.